Design and Build a Network Monitoring System Using Nagios at PT. Telkom Access - Muhammad Tri Madja Pandia; Fachrid Wadly (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The implementation of an effective network monitoring system is very important for companies to maintain service performance and availability. This research aims to design and implement a network monitoring system using Nagios at PT. Telkom Access. The research methodology includes direct observation, interviews with related parties, and literature studies. The results of the study show that the implementation of Nagios in PT. Telkom Access enables real-time monitoring of network devices and servers, provides early notifications of potential problems, and facilitates rapid response to disruptions. The system is integrated with the Ubuntu Server 22.04 operating system and utilizes the Nagios plugin to monitor various performance parameters. In conclusion, Nagios provides reliable and effective solutions to increase service availability, optimize network performance, and ensure customer satisfaction at PT. Telkom Access.